Kant’s imitatio Christi - Whistler, Daniel (International journal for philosophy of religion, 2010)
This article retrieves Kant’s imitatio Christi as a viable alternative to the recent construal of mimesis as a universal human desire, in particular to Ward’s reformulation of the imitatio Christi in such terms (in which the human condition is defined by an intrinsic desire for God as other). Kant’s writings participate in a very different debate on imitation (one sceptical of its ethical value), and this plays out as a continual ambivalence towards the concept in his work. Kant’s imitatio Christi, however, does, I contend, make possible a moral form of imitation by characterising it as a rational and intersubjective debate upon the good. Imitating Christ becomes part of human ethical living in the world.